TEKNIK MEMBACA - MENGINGAT-INGA-T BAHAN PENULISAN KARYA LLMIAH - Kertopati, Ton (Universitas Prof. Dr. Moestopo (Beragama), 2007)
As we are seen, personal progression involves the development of knowledge, skills and attitudes in all areas and the development of whole person as an individual and as a member of society. How ever learning as a tool by itself can tie limited ettectiveness. What is learning? Learning is defined as a reJatively permanent change in behavior that occurs. For most student an effective approach is to scan _the study guide, the chapter focus and study outline sections. Read the text carefully and making notes. Designing or enriching activities intended to help the students to gain more knowledge and skills.A team researchers developed a program to help students how to read with a purpose. How to get them more actively involved in the material they read. How to read effectively and productively. Reading and remembering technique, a more recent variation of this technique is called the PQ4R technique introduced by Thomas and Robinson ( 1972).